PEMBATALAN JUAL BELI TANAH AKIBAT PEMALSUAN DATA DI HADAPAN NOTARIS - Reydo Zulfiq (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT Land binding sale are a common practices seen in society as well in notary offices. Land binding sales are processes prior to land purchase agreements, done by Land Deeds Officers. In Article 37 point (1) in Law of Indonesia number 24 year 1997 in Government Regulation on Land Regulation mentioned that land transition needed an authentic deeds produced by Land Deeds Officers appointed by the Government. Approach method used was empirical juridical. Specification used in this research was analytical descriptive.Legal effect on authentic deeds within false information that caused disputes can be sued to court. The injured party might file civil to court to be sentenced by the trial judge in order to call for cancellation deed. By then, the deeds do not have the force of law. The deeds considered as legally defect. By the deeds cancellation is sentenced by the judge, it is due retroactively since the deeds produced.. Keywords : Land binding sale